TINGKAT PENERIMAAN PAJAK JIKA DIPENGARUHI OLEH KEPATUHAN WAJIB PAJAK DAN SANKSI PERPAJAKAN PADA KPP PRATAMA BANDUNG CICADAS - Aldila, Ilda Fitri; Leviany, Tevi; Herawati, Heti (Universitas Sangga Buana, 2024)
This study aims to examine the influence of taxpayer compliance and tax sanctions on tax revenue at KPP Pratama Bandung Cicadas during the period of 2018–2022. The research was conducted using an associative descriptive method and produced the following results: (1) taxpayer compliance has a significant effect on tax revenue, (2) tax sanctions do not have a significant effect on tax revenue, and (3) taxpayer compliance and tax sanctions simultaneously have a joint effect on tax revenue. Taxpayer compliance (X1) and tax sanctions (X2) together contribute 60.7% to the variation in tax revenue.